Juvenile Crime and Punishment - Levitt, Steven D. (Journal of Political Economy, 1998)
Over last two decades punitiveness of juvenile justice system has declined substantially relative adult courts. During that same time period juvenile violent rates have grown almost twice as quickly as adult crime rates. This paper examines degree to which those two empirical observations are related, finding that changes in relative punishments can account for 60 percent of differential growth rates in juvenile and adult violent between 1978 and 1993. Juvenile offenders appear be at least as responsive sanctions as adults. Moreover, sharp changes in criminal involvement with transition from juvenile adult court suggest that deterrence, rather than simply incapacitation important role. There does not, however, appear be a strong relationship between the punitiveness of juvenile justice system that a cohort faces and extent of involvement for that cohort later in life.